1998
DOI: 10.3354/meps165247
|View full text |Cite
|
Sign up to set email alerts
|

Induction of gene expression of the chaperones <t-1>14-3-3 and HSP70 by PCB 118 (2,3',4,4',5-pentachloro<t0>biphenyl) in the marine sponge Geodia cydonium:novel biomarkers for polychlorinated biphenyls

Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous industrial compounds found in almost every component of the terrestrial and marine ecosystem. Most of the PCB congeners bind to the aryl hydrocarbon receptor and in turn cause expression of stress response genes. Here we report for the first time that PCB 118 acts in the marine sponge Geodia cydoniurn as an inducer of 2 chaperones, the 14-3-3 protein(s) (a protein targeting molecule) and the heat shock protein HSP70 (a chaperone, primarily involved in folding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 30 publications
0
68
0
Order By: Relevance
“…65,66 RNA (total) samples (5 mg) were electrophoresed in a formaldehyde/1% agarose gel and blotted onto Hybond N + membrane following the manufacturer's instructions (Amersham; Little Chalfont, Buckinghamshire; UK). Hybridization was performed with the 586 nt long GCBHP2 fragment (spanning nt 83 to nt 668 of the ORF) in HighNaDodSO 4 hybridization Buffer (7% NaDodSO 4 , 50% formamide, 56SSC, 0.1% Na-laurylsulfate, 50 mM Na 3 PO 4 [pH 7.0] and 2% of blocking reagent [Roche]) at 428C.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…65,66 RNA (total) samples (5 mg) were electrophoresed in a formaldehyde/1% agarose gel and blotted onto Hybond N + membrane following the manufacturer's instructions (Amersham; Little Chalfont, Buckinghamshire; UK). Hybridization was performed with the 586 nt long GCBHP2 fragment (spanning nt 83 to nt 668 of the ORF) in HighNaDodSO 4 hybridization Buffer (7% NaDodSO 4 , 50% formamide, 56SSC, 0.1% Na-laurylsulfate, 50 mM Na 3 PO 4 [pH 7.0] and 2% of blocking reagent [Roche]) at 428C.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…These proteins act to protect the organism from cell protein damage due to exposure to a wide variety of stressors, including elevated temperature (Lindquist, 1986;Sanders, 1993), cold shock (Nunamaker et al, 1996), oxidative stress (Lindquist, 1986), increased UV irradiation (Sanders, 1993), extreme pH (Koziol et al, 1996), osmotic stress (Burg et al, 1996), heavy metals (Köhler et al, 1992;Miller et. al., 1992;Sanders, 1993;Vedel and Depledge, 1995), xenobiotics (Sanders, 1993), and other pollutants (Lindquist, 1986;Blom et al, 1992;Pomerai, 1996;Wiens et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The PCR reaction was carried out at an initial denaturation at 95°C for 3 min, then 30 amplification cycles at 95°C for 30 S, 52°C for 45 S, 74°C for 1.5 min, and a final extension step at 74°C for 10 min. The reaction mixture was as described earlier (Wiens et al 1998). The longest fragment of -500 bp was used and completed by primer walking as described by Ausubel et al (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Studies revealed that sponges can cope with organic pollutants and organismic attacking invaders by (1) cellular defense systems, e.g. heat-shock proteins (Koziol et al 1997), targeting chaperones like the 14-3-3 protein(s) (Wiens et al 1998), multidrug resistance (MDR) (reviewed in Kurelec 1997) or thioredoxin (Wiens et al 1999) and by (2) organismic protection, including a well-developed immune system ) and bioactive secondary metabolites (Sarma et al 1993, Proksch 1994. Recently, we also identified the second MDR-system, related to the POHl Lpad one homologoue] mechanisms (Spataro et al 1997), which is thought to 'eliminate' pollutants via an enzymatic route (Krasko et al 2000).…”
Section: Introductionmentioning
confidence: 99%